Mourning Doves in Florida - William M. Giuliano; James F. Selph; Kurt Hodges; Nick Wiley (EDIS)
WEC-226, a 4-page illustrated fact sheet by William M. Giuliano, James F. Selph, Kurt Hodges, and Nick Wiley, describes the only dove species native to the state of Florida. Includes sections on distribution and status, biology, habitat, management, and hunting. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, August 2007.